1977
DOI: 10.1099/00221287-98-2-369
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Regulatory Function for Glutamine Synthetase Protein in the Synthesis of Glutamate Dehydrogenase and Nitrite Reductase in Escherichia coli K12

Abstract: Synthesis of glutamine synthetase (GS) in anaerobic batch cultures of Escherichia coli was repressed when excess NH,+ was available, but derepressed during growth with a poor nitrogen source. In wild-type bacteria there was only a weak inverse correlation between the activities of GS and glutamate dehydrogenase (GDH) during growth in various media. No positive correlations were found between the activities of GS and nitrite reductase, or between GS and cytochrome cSS2: both of these proteins were synthesized n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Formate-nitrate oxidoreductase activity was determined with bacteria which had been grown for 16 h without aeration in 800 ml minimal medium (Newman & Cole, 1977) supplemented with 27 mM-glucose and 6.5 g nutrient broth 1-1 (Oxoid CM1) (Lambden & Guest, 1976). Cell membranes resuspended in 50 mMNa+/K+ phosphate buffer pH 7.4 were incubated at 37 "C with 40 mM-Na+ formate and 40 m -K N O , under a stream of N,.…”
Section: E T H O D Smentioning
confidence: 99%
See 2 more Smart Citations
“…Formate-nitrate oxidoreductase activity was determined with bacteria which had been grown for 16 h without aeration in 800 ml minimal medium (Newman & Cole, 1977) supplemented with 27 mM-glucose and 6.5 g nutrient broth 1-1 (Oxoid CM1) (Lambden & Guest, 1976). Cell membranes resuspended in 50 mMNa+/K+ phosphate buffer pH 7.4 were incubated at 37 "C with 40 mM-Na+ formate and 40 m -K N O , under a stream of N,.…”
Section: E T H O D Smentioning
confidence: 99%
“…Genetic methods. Lennox (1955) broth was used for conjugation and transduction experiments, as described by Newman & Cole (1977). Unless otherwise stated, a virulent derivative of bacteriophage Plkc was used to prepare lysates for transduction experiments.…”
Section: E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation
“…However, synthesis of these anaerobic enzymes is independent of Ntr control (32), and anaerobic cultures actually excrete ammonia into the medium (6). Therefore, this does not represent a true assimilatory process, and E. coli does not assimilate nitrate or nitrite during aerobic growth (reviewed in reference 38).…”
mentioning
confidence: 99%
“…But it was also suggested that the GDH in E. coli is regulated differently (COLE et aZ. 1974, NEWNAN andCOLE 1977). The occurrence of the bistability in th.…”
Section: Discussionmentioning
confidence: 99%